2017
DOI: 10.1007/s00455-017-9799-x
|View full text |Cite
|
Sign up to set email alerts
|

Patient Experiences of Swallowing Exercises After Head and Neck Cancer: A Qualitative Study Examining Barriers and Facilitators Using Behaviour Change Theory

Abstract: Poor patient adherence to swallowing exercises is commonly reported in the dysphagia literature on patients treated for head and neck cancer. Establishing the effectiveness of exercise interventions for this population may be undermined by patient non-adherence. The purpose of this study was to explore the barriers and facilitators to exercise adherence from a patient perspective, and to determine the best strategies to reduce the barriers and enhance the facilitators. In-depth interviews were conducted on thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 49 publications
(63 reference statements)
1
48
0
Order By: Relevance
“…With a median adherence of 78% the results may still suggest that the frequent supervision and individualized exercise prescription has a decisive effect on adherence. In accordance, Govender et al [23] found that appointments with a therapist and motivational support enhanced adherence to a swallowing exercise program among HNC patients. Also, Perry et al [6] pointed out that the exercise burden in preventive swallowing trials for HNC patients often become so onerous that it causes patients to drop out of the trials.…”
Section: Discussionmentioning
confidence: 68%
“…With a median adherence of 78% the results may still suggest that the frequent supervision and individualized exercise prescription has a decisive effect on adherence. In accordance, Govender et al [23] found that appointments with a therapist and motivational support enhanced adherence to a swallowing exercise program among HNC patients. Also, Perry et al [6] pointed out that the exercise burden in preventive swallowing trials for HNC patients often become so onerous that it causes patients to drop out of the trials.…”
Section: Discussionmentioning
confidence: 68%
“…The framework is intended to be comprehensive, parsimonious and applicable to all behaviours. COM-B has been widely applied to many different types of behaviours, including studies of audiologists’ behavioural planning [23], adherence to swallowing exercise [24] and promoters and barriers to being vaccinated and taking antiviral drugs [25].…”
Section: Methodsmentioning
confidence: 99%
“…This would enable a clearer understanding of how to create change in the behavior of nurses and care staff, for example, by thinking about their capabilities, opportunities and motivators. Of note, behavior change theory is an approach which is increasingly used in other speechlanguage pathology interventions (Govender et al, 2017;Johnson et al, 2016).…”
Section: Training Interventionsmentioning
confidence: 99%